Comparative federalism : states' rights and national power - McWhinney, Edward, 1924- (Toronto : University of Toronto Press, 2019)
In contrast to the views current only a few years ago, when federalism as a system of government was regarded, in academic circles in North America at least, as passe and even reactionary, there is today throughout the world, and especially in Western Europe, a tremendous interest in the federal idea. It is seen as a dynamic, even revolutionary idea, and it has been seized on as the best institutional device available for assisting and promoting the integration of the Western European countries - one which offers, moreover, the best opportunities for preserving liberal, pluralistic ideals in an era of strong centralized governments. The interest in federalism and in supranational integration makes essential a definitive study of the working practice of federal law and government in those societies where federalism has been long in operation.-
In these stimulating and thoughtful essays Professor McWhinney brings a fresh and up-to-date view to bear on the nature of federalism, the problems of such a system of government in the complications of modern times, and the role of the reviewing courts within that system. He has focused his discussion on those countries where the federal form does mirror genuine social divisions and conflicts - in particular the United States and Canada as classical models of the federal idea, and the Federal Republic of Germany as an area where the federal idea is being worked out freshly, with a special new court, and against a different social background.-
In thus treating of federalism on a comparative basis, Professor McWhinney has been concerned with the frequent shifts and accommodations of governmental policy and actions, with the actual processes of resolving conflicts and competitions of interests, and with the systematic, settled practices of self-restraint and mutual give-and-take, all of which are necessary for the functioning, and for the life itself, of a federal state. In this emphasis on basic social and political problems, which are reflected in the decision of the highest courts, rather than on a narrow and abstract interpretation of the distribution of powers between different jurisdictions, Professor McWhinney has brought into new relationship matters of perennial occurrence and importance within any federal system. His study will be of interest and value not only to students of federalism but to all those concerned with public affairs.
Frontmatter -- Preface -- Contents -- 1. The Utility of Federalism in a Revolutionary Age -- 2. The Philosophy of Federalism: Federalism and Legal Pluralism -- 3. Umpiring the Federal System: The Special Role of the Supreme Court in a Federal State -- 4. Federalism and the Foreign Affairs Power -- 5. Federalism and Defence of the Constitutional Order -- 6. Social Policy: States' Rights, Minority Rights, and the Limits of Unity and Diversity -- 7. Federalism and the Principle of Federal Comity -- 8. The Relevance of Federalism for Contemporary Constitution-Making -- Index
Obsahuje bibliografické odkazy a rejstřík
Elektronická reprodukce.
Keywords: federalismus; federal government; e-knihy online; e-books online